2021
DOI: 10.1108/imds-12-2020-0697
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid analysis for understanding contact tracing apps adoption

Abstract: PurposeThis study aims to explore the adoption of contact tracing apps through a hybrid analysis of the collected data using structural equation modelling (SEM) and artificial neural networks (ANN), leading to the identification of the critical determinants for the adoption of contact tracing apps in Australia.Design/methodology/approachA research model is developed within the background of the unified theory of acceptance and use of technology (UTAUT) and the privacy calculus theory (PCT) for investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 30 publications
2
49
2
1
Order By: Relevance
“… Chan and Saqib (2021) (on French, Australian and US populations) Xs: Social influence, facilitating condition, effort expectancy, performance expectancy, perceived privacy risk Mediator: Perceived value of information disclosure Y: Adoption intention The study shows that effort expectancy, perceived value of information disclosure and social influence are critical for adopting contact-tracing apps. Duan and Deng (2021) (on an Australian population) Time 1: Xs: Social influence, reciprocal benefits, perceived health benefits, Privacy concerns Ys: Adoption intentions, willingness to rely Time 2: Xs: Social influence, reciprocal benefits, perceived health benefits, privacy concerns Mediators: Adoption intentions, willingness to rely Y: Usage intentions Reciprocal benefits positively influence technology acceptance. Time is an important factor during a crisis, and it will influence citizen acceptance of the app.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“… Chan and Saqib (2021) (on French, Australian and US populations) Xs: Social influence, facilitating condition, effort expectancy, performance expectancy, perceived privacy risk Mediator: Perceived value of information disclosure Y: Adoption intention The study shows that effort expectancy, perceived value of information disclosure and social influence are critical for adopting contact-tracing apps. Duan and Deng (2021) (on an Australian population) Time 1: Xs: Social influence, reciprocal benefits, perceived health benefits, Privacy concerns Ys: Adoption intentions, willingness to rely Time 2: Xs: Social influence, reciprocal benefits, perceived health benefits, privacy concerns Mediators: Adoption intentions, willingness to rely Y: Usage intentions Reciprocal benefits positively influence technology acceptance. Time is an important factor during a crisis, and it will influence citizen acceptance of the app.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“… Bui Thanh Khoa (2020) [ 109 ] Mobile banking services Perceived credibility Information interest Perceived control Privacy concern Perceived vulnerability Perceived value It was found that all the constructs of perceived benefits and perceived costs have a remarkable effect on perceived value in the mobile banking services context. Duan and Deng, H. (2021) [ 110 ] Contact tracing apps Performance expectancy Perceived privacy risk Perceived value of information disclosure The analysis result confirmed that performance expectancy and perceived privacy risks are indirectly significant on the adoption through the influence of perceived value of information disclosure. Zhu et al (2021) [ 111 ] mHealth apps Perceived benefits Privacy concern Disclosure intention When determining information disclosure, the users’ benefits perception for using mHealth applications is two or three times more influential than their privacy concerns.…”
Section: Table A1mentioning
confidence: 76%
“…The information system literature about the technology adoption model primarily predicts behavioral intention, usage intention, or adoption intention as the dependent variable. Most of the studies investigate this variable predictive power through PLS-SEM ( 10 , 34 , 39 ) or CB-SEM ( 35 37 , 41 ). One of the primary criteria used to examine the model's predictive capacity is the coefficient of determination ( R 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature review has identified a few studies that employed a two-stage analysis to investigate CTA adoption. Specifically, Duan and Deng ( 37 ) employed CB-SEM with an artificial neural network (ANN) approach to investigate the CTA adoption through the lens of the unified theory of acceptance and use of technology and privacy calculus theory in Australia. In contrast, the study by Nguyen et al ( 39 ) investigated the extended technology adoption model through PLS-SEM and fuzzy set/qualitative comparative analysis (fsQCA).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation